Allele-specific Gene Silencing of Mutant mRNA Restores Cellular Function in Ullrich Congenital Muscular Dystrophy Fibroblasts - Satoru Noguchi; Megumu Ogawa; Genri Kawahara; May Christine Malicdan; Ichizo Nishino (Elsevier, 2014)
Ullrich congenital muscular dystrophy (UCMD) is an inherited muscle disorder characterized clinically by muscle weakness, distal joint hyperlaxity, and proximal joint contractures. Sporadic and recessive mutations in the three collagen VI genes, COL6A1, COL6A2, and COL6A3, are reported to be causative. In the sporadic forms, a heterozygous point mutation causing glycine substitution in the triple helical domain has been identified in higher rate. In this study, we examined the efficacy of siRNAs, which target point mutation site, on specific knockdown toward transcripts from mutant allele and evaluated consequent cellular phenotype of UCMD fibroblasts. We evaluated the effect of siRNAs targeted to silence-specific COL6A1 alleles in UCMD fibroblasts, where simultaneous expression of both wild-type and mutant collagen VI resulted in defective collagen localization. Addition of mutant-specific siRNAs allowed normal extracellular localization of collagen VI surrounding fibroblasts, suggesting selective inhibition of mutant collagen VI. Targeting the single-nucleotide COL6A1 c.850G>A (p.G284R) mutation responsible a sporadic autosomal dominant form of UCMD can potently and selectively block expression of mutant collagen VI. These results suggest that allele-specific knockdown of the mutant mRNA can potentially be considered as a therapeutic procedure in UCMD due to COL6A1 point mutations.